Rational preparation of Ag and Au bimetallic catalysts for the hydrocarbon-SCR of NOx: sequential deposition vs. coprecipitation method - More, Pavan M.; Nguyen, D. L.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Nuns, N.; Girardon, J. S.; Dujardin, Christophe; Lancelot, Christine; Mamede, Anne-Sophie; Granger, P. (Applied Catalysis B-Environmental, 2015)
This study emphasizes the importance of the preparation method for bimetallic Au-Ag catalysts supported on alumina in the selective reduction of NOx by hydrocarbons with gas feed compositions representative of diesel fuelled engine exhaust gas. An optimal balance between oxidative and reductive surface properties is obtained when Au and Ag are successively introduced. Significant re-dispersion processes take place when the catalyst runs at 500 degrees C leading to a gain in activity at low temperature and ascribed to a better interaction between Au and Ag species. Co-precipitation leads to a preferential formation of intermetallic Au-Ag particles which is detrimental to the catalytic performances. Aging at 500 degrees C leads to a significant particle sintering and a strengthening of the metallic character. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Au-Ag particles; Co-precipitation; DeNO(x) reaction; HC-SCR